2017
DOI: 10.1111/1462-2920.13872
|View full text |Cite
|
Sign up to set email alerts
|

Nitrifier‐induced denitrification is an important source of soil nitrous oxide and can be inhibited by a nitrification inhibitor 3,4‐dimethylpyrazole phosphate

Abstract: Soil ecosystem represents the largest contributor to global nitrous oxide (N O) production, which is regulated by a wide variety of microbial communities in multiple biological pathways. A mechanistic understanding of these N O production biological pathways in complex soil environment is essential for improving model performance and developing innovative mitigation strategies. Here, combined approaches of the N- O labelling technique, transcriptome analysis, and Illumina MiSeq sequencing were used to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 70 publications
4
23
0
Order By: Relevance
“…The limitation of Nitrosospira but not Nitrososphaera by DCD has been shown also in a paddy field soil and in microcosms of Nitrosospira multiformis but not Nitrososphaera viennensis (Shen et al, 2013;Fu et al, 2018). In studies of nitrification in agricultural soils, DMPP inhibited AOB expression under neutral pH conditions (Shi et al, 2016(Shi et al, , 2017. In a Chinese vegetable soil, DMPP rather than DCD was revealed to be the more effective inhibitor of N 2 O-producing AOB rather than AOA, although the N source urea was also amended with manure (Kou et al, 2015).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The limitation of Nitrosospira but not Nitrososphaera by DCD has been shown also in a paddy field soil and in microcosms of Nitrosospira multiformis but not Nitrososphaera viennensis (Shen et al, 2013;Fu et al, 2018). In studies of nitrification in agricultural soils, DMPP inhibited AOB expression under neutral pH conditions (Shi et al, 2016(Shi et al, , 2017. In a Chinese vegetable soil, DMPP rather than DCD was revealed to be the more effective inhibitor of N 2 O-producing AOB rather than AOA, although the N source urea was also amended with manure (Kou et al, 2015).…”
Section: Discussionmentioning
confidence: 84%
“…In a Chinese vegetable soil, DMPP rather than DCD was revealed to be the more effective inhibitor of N 2 O-producing AOB rather than AOA, although the N source urea was also amended with manure (Kou et al, 2015). In studies of nitrification in agricultural soils, DMPP inhibited AOB expression under neutral pH conditions (Shi et al, 2016(Shi et al, , 2017. The different success of the nitrification inhibitors appears to be a function of temperature, Cu-levels, and variation in abundance, genetic potential and/or expression levels of the targeted nitrifiers (Ruser and Schulz, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this process, AOB possess machinery that reduces NO 2 – to N 2 O via a nitric oxide (NO) intermediate ( Ritchie and Nicholas, 1972 ; Shaw et al, 2006 ). Shi et al (2017) showed that nitrifier denitrification is an important pathway leading to high N 2 O production (10.5–54.5%) in alkaline cropping soils (pH 7.2); however, heterotrophic denitrification accounted for a the largest proportion of total N 2 O production (∼83%) in acid soils (pH 4.9). Recently, Caranto et al (2016) demonstrated another direct enzymatic pathway from NH 2 OH to N 2 O under anaerobic conditions, which is mediated by cytochrome P460.…”
Section: Introductionmentioning
confidence: 99%
“…This would involve slow release ammonium fertilizers, possibly combined with selective inhibitors. To reduce the N 2 O emission from nitrifier coupled denitrification (Shi et al ., ), any measure that enhances the activity of N 2 O reductase activity (see below) will be effective. These considerations are also relevant for understanding the N 2 O emission from industrial waste water treatment plants, in which nitrification/nitritation reactors are the strongest emitters of N 2 O, and their emission is enhanced by incomplete aeration (Kampschreur et al ., ).…”
mentioning
confidence: 99%